Importância e valor nutricional do pólen de Cocos nucifera para abelhas africanizadas cultivadas no litoral alagoano - Moura, Jackeline Targino de (2014)
Large coconut fields and mangroves characterize Alagoas coastline. The present study aimed at determining the nutritional content of Cocos nucifera pollen and its participation in the diet of Africanized honeybees reared in that environment. A palinological approach was used to characterize and quantify pollen grains. Freshand bee-collected pollen were harvested and analyzed for their nutritional content. Dry matter, crude protein, fat and ash, as well as some minerals and amino acid and fatty acid composition were determined. Coconut pollen showed a bilateral symmetry and three elongated apertures. The amount of bee-collected pollen harvested during this study varied from 13.2 g/day to 32.9 g/day. Nine pollen types were found in the beecollected samples analyzed. Coconut pollen wasthe dominant pollen type (>45%) in all samples. In November its participation reached 72.23%. Protein content of fresh coconut pollen appeared to be 33.48% dry weight. Lipid content was 6.61% dry weight and ash 3.28%. Eleven minerals were quantified in fresh coconut pollen. Macro minerals appeared to be at higher levels than those reported in the literature for Brazilian bee-collected pollen. Micro minerals presented compatible values on average, but it is to be noted the high levels of iron (245.15 ppm). Nineteen amino acids were found in fresh coconut pollen, including the ten identified as essential for honeybees. Essential amino acids were present in higher amounts than the required minimum levels for honeybee development, with the exception of tryptophan. The lipid fraction of Cocos nucifera pollen includes 21 fatty acids, palmitic (C-16), oleic (C- 18:1), linoleic (C-18:2) and linolenic (C-18:3) acids being the dominant ones. To our knowledge, this study is the first one to determine the nutritional value of the pollen of asingle species important for beekeeping in Brazil.